(untitled) (Significação: Journal of Audiovisual Culture, 2003)
This work analyze the interactive process who has the public space like agent and scene. In this way, space sheltes some cultural, communicative and semiotc characteristics and he suffers social and technological shocks. In consequence he exceeds physical and territorials limits and shows differents meaningsthrough cosmopolitan, peersuasive and virtual public space.